Citation Fall Index (CFI): An Indicator to Measure the Centripetal Nature of Accretion of Citation - Dutta, Bidyarthi (Journal of Information and Knowledge, 2023)
That citation attracts citation and fairly-cited items quickly become highly-cited, whereas poorly-cited or uncited items are hardly cited even after a long span is a known phenomenon referred to as the ‘Cumulative Advantage’ process (“Success breeds success”). The citation distribution always shows a highly skewed pattern to a very small number of core groups. This paper has proposed a fundamental formula to measure the change in relative fall in citation count with a corresponding change in the ranking of different kinds of cited items (author, journal, article, etc.). Two new indicators are mathematically developed here, the names given to which are, Relative Citation Fall (RCF) and Citation Fall Index (CFI). These indicators will be tested for different kinds of cited items in different subject domains to quantitatively measure citation skewness in future studies.